Higher education system placement in the innovation sphere in solving staffing innovative economy problem. Part I - Yu. N. Kafiyatullina; I. S. Prokhorova (Вестник университета)
The article analyzes specifics of training personnel in innovation management in Russia. The object of the study is the direction of the Innovation training, which implements the methodology of training specialists in innovation management in all spheres of economy. The purpose of the article is to assess compliance of the training methodology in innovation management with the requirements of the modern concept of practice-oriented education and conducting fundamental and applied research in universities that are in demand in innovative economy. The objective is to formulate the problem of implementing such requirements for higher education system as adaptability of graduates and their ability to implement projects and facilitate innovative development. The research is based on the application of Basadur’s simplex method to solve non-standard management problems and forms of comprehensive understanding of training personnel problems and use of professional competencies of innovation manager in the project education methodology for entrepreneurial university model implementation. As a result, the task of forming a technical universities collaboration with a pool of technological uncommercial startups has been formulated, as well as with universities that train innovation managers as specialists in promoting a startup to market.